The use of mid-trial reviews for design modifications in small scale clinical studies - Sooriyarachchi, M.R.; Jayatillake, R.V.; Ranganath, H.; Eddleston, M. (Elsevier, 2010)
Many clinical studies such as those in the areas of toxicology, early phase clinical trials and bioequivalence studies use small samples due to the high cost of experimentation. These studies test hypotheses based on small samples. These small samples result in low power and therefore even if the alternative hypotheses may be true the chance of it being rejected is low. The sample size is determined in an ad-hoc way and no proper scientific approach is used. Sample size calculations for clinical studies are usually conducted to determine the total number of patients needed to satisfy a specified power requirement, and their validity is dependent on pre-trial knowledge of nuisance parameters and distributional and modelling assumptions. Another short coming is that often hypotheses are tested without checking the assumptions required by the test. This paper looks at design reviews in the context of small samples. It examines several design modifications done with asmall internal pilot study. In the past similar techniques have been applied to large scale studies but it sperformance is yet to be established in small scale clinical studies thus the contribution of this paper is in justifying the validity of these techniques for small samples too. The methodology is illustrated on an uncontrolled observational toxicology study. In this paper simulations will be presented showing that the design modifications would not influence the type-I error rate and that these would be successful in preserving the power, and the implementation of the design review procedure will be described.
Keywords: Internal pilot study Mid-trial design review Normal error linear model Sample size reestimation Testing distributional and modelling assumptions